EVALUATION OF Cr(VI) REMOVAL PROCESS IN AQUEOUS SOLUTIONS USING CARNATION CROP WASTE COMPOST - Castillo, Elianna (2016)
This paper presents a study that aimed to determine the mechanism of a process for Cr(VI) removal from aqueous solutions, using compost of carnation crop residues as the adsorbent. We assessed whether the microbiota present in the absorbent material affected the removal of Cr(VI) using respirometric measurements and evaluating the removal capacity using sterilized and not sterilized compost. Additionally, the compost was analysed before and after carrying out the Cr(VI) removal process, by quantification of the acidic functional groups and kinetic monitoring of pH, conductivity and redox potential difference. The results showed that, under the conditions used, the microorganisms present in the compost did not affect the process of Cr(VI) removal and that the mechanism can be described by an adsorption model coupled to the reduction, were this adsorption is mainly done on the acidic functional groups (carboxylic and phenolic-hydroxylic). Base on this information, a mechanism of 7 reactions was constructed to describe the removal process. The kinetic constants for each reaction were optimized with a sensitivity analysis process. The proposed mechanism was verified by numerical simulations and a good agreement was found between experimental and simulated data.